Peran Keluarga dalam Mengatasi Penurunan Motivasi Ibadah pada Remaja di Era Digital - Muhammad Faisal Arrayyan; Vismaia Nur Fitriani; Astuti Darmiyanti (Jurnal Budi Pekerti Agama Islam, 2026)
The development of digital technology has brought various changes to the lives of adolescents, including religious aspects. Easy access to social media and various forms of digital entertainment can affect adolescents' motivation to practice religious worship if not balanced with appropriate supervision and guidance. This study aims to determine the role of families in overcoming the decline in religious motivation in adolescents in the digital era. The study used a qualitative approach with descriptive methods. The research subjects consisted of one parent and one adolescent selected using purposive sampling techniques. Data collection was conducted through interviews, observation, and documentation. The data obtained were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study were obtained through the instillation of religious values, providing advice, habituating worship, and parental role models. In addition, good communication and a religious atmosphere within the family also support the growth of religious awareness in adolescents. This study also found that digital media has both positive and negative influences on adolescents' religious lives. Therefore, family guidance is needed so that technology can be used wisely and support adolescents' religious development. The research findings indicate that family involvement is a crucial factor in shaping and maintaining adolescents' religious motivation amidst the challenges of the digital era.